Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
y = - 5x² - 10x + 2
Step-by-step explanation:
y = - 5(x + 1)² + 7 ← expand (x + 1)² using FOIL
= - 5(x² + 2x + 1) + 7 ← distribute parenthesis by - 5
= - 5x² - 10x - 5 + 7 ← collect like terms
= -5x² - 10x + 2 ← in standard form
Answer: y = -5x² - 10x + 2
Step-by-step explanation:
Given quadratic function
y = -5 (x + 1)² + 7
Given requirement
Quadratic Standard Form: y = ax² + bx + c
Simplify the exponents
y = -5 (x + 1) (x + 1) + 7
y = -5 (x² + x + x + 1) + 7
y = -5 (x² + 2x + 1) + 7
Expand the parenthesis by distributive property
y = (-5) · x² + (-5) · 2x + (-5) · 1 + 7
y = -5x² + (-10x) + (-5) + 7
y = -5x² - 10x - 5 + 7
Combine like terms
[tex]\Large\boxed{y=-5x^2-10x+2}[/tex]
Hope this helps!! :)
Please let me know if you have any questions
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.